3015 Enhancing Outcomes in Childcare Settings for Young Children with Behavior Disorders: An Examination of Conscious Discipline Implementation. (27th March 2019) - John, Sufna Gheyara; Edge, Nicola; Cucciare, Michael; Long, Nicholas
Abstract : OBJECTIVES/SPECIFIC AIMS: 1. Identify the extent of CD implementation for trained childcare teachers. 2. Explore teacher perspectives on the impact of CD. 3. Explore teacher perspectives on barriers and facilitators to full implementation of CD. METHODS/STUDY POPULATION: We conducted a survey with 267 childcare teachers who had been trained in CD across the state, representing early childhood educational environments in urban and rural settings. Specific questions were asked related to level of CD implementation, perceived benefit, and facilitators/barriers to full implementation. A random subset of the sample (8 teachers) participated in a subsequent focus group to explore survey themes in greater depth. Focus group members were asked about their rationale for attending CD training, CD implementation (including barriers/facilitators to full implementation), and perceived impact on their classrooms. The focus group was recorded and transcribed to capture questions and comments. RESULTS/ANTICIPATED RESULTS: Objective 1: 1. 30% of teachers reported full implementation of CD. 2. 50% of teachers reported partial implementation of CD. Objective 2: 1. The vast majority of teachers (95%) agreed that CD had a positive impact on their classroom, including better structure and enhanced relationships with the children. 2. The vast majority of teachers (85%) agreed that CD had a positive impact on the children in their classroom, including increases in problem-solving abilities and self-control. Objective 3: 1. Most teachers (71%) reported experiencing barriers to CD implementation, with the majority of those surveyed (93%) stating that additional implementation support would be helpful. 2. The top three barriers to implementation elicited in survey and focus groups included uncertainty regarding how to begin implementing CD in the classroom, lacking materials for CD implementation, and lacking time to focus on applying knowledge from training into the classroom. 3. The top three facilitators for implementation elicited in survey and focus groups included coaching support for teachers, training agency leadership in CD, and greater perceived impact of CD. DISCUSSION/SIGNIFICANCE OF IMPACT: Childhood disruptive behaviors are among the most frequent reasons for referral to specialized services in and out of the classroom (Sukhodolsky, Smith, McCauley, Ibrahim, & Piasecka, 2016). Disruptive and aggressive behaviors are problematic, not only for victims of children who are aggressive but also for aggressive children as they age. Although effective treatments exist, the level of effective implementation of these interventions are understudied. These results demonstrate that 2/3 of teachers trained in CD are not fully implementing the model and provides concrete barriers and facilitators to current implementation. These data will provide the initial foundation for the development of a targeted implementation strategy that supports full implementation of CD within early childhood education settings.